Zvýšení badatelského potenciálu jednoduchých přírodovědných pokusů - Vydrová, Lucie (Univerzita Karlova, Pedagogická fakulta, 2023)
This bachelor thesis deals with the issue of research-based teaching and its application in chemistry education. In the theoretical part, the division, meaning and position of the framework curriculum in primary schools is presented. The next part deals with inquiry- based teaching, its definition, advantages and disadvantages that it can bring to chemistry teaching and education in general. The paper then focuses on motivation, its types, how it can be used in teaching and the factors affecting motivation. In the practical part, the findings from the previous chapters are used to develop two worksheets to support inquiry- based activities. They are designed to make it as easy as possible for pupils to understand the material themselves. The two worksheets are divided into two parts. The first is for the teacher, divided into several sections to make it easy to understand the teacher's necessary preparation for the lesson and the procedures and outcomes expected of the pupils. There is also a section of hints, called 'tip-cards', to help pupils if they get lost in the process. The second part is for pupils. The worksheet has been designed to support as much as possible the exploratory style of teaching and, more importantly, the independence of the pupils. Emphasis is also placed on linking. Tato bakalářská práce se zabývá problematikou badatelsky pojaté výuky a jejího uplatnění ve výuce chemie. V teoretické části je přiblíženo rozdělení, význam a pozice rámcového vzdělávacího programu na základních školách. Další část se zabývá badatelsky orientovanou výukou, jejím vymezením, výhodami a nevýhodami, které může do výuky chemie a celkově do vzdělávání přinést. Poté se práce zaměřuje na motivaci, její typy, způsoby využití ve výuce a faktory ovlivňující motivaci. V praktické části jsou použity poznatky z přechozích kapitol, na základě kterých byly vytvořeny dva pracovní listy pro podporu badatelských aktivit. Jsou koncipovány tak, aby žáci sami a co nejsnadněji pochopili učivo. Oba pracovní listy jsou rozděleny ...